(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
Purpose – this paper aims to analyse the business efficiency of the Alibaba platform at the beginning and during the COVID-19 crisis. Methodology/Design - The research is based on the official financial reports of the platform as well as on the reports of other specialized agencies that monitor the platform industry. The study focuses on an analysis of the financial indicators of the business. It compares the financial indicators with an analysis of the data on the trend of the user community on the platform. The results - the study’s findings did not find a major impact of the COVID-19 pandemic on the overall business results of the Alibaba platform. The survey results confirmed changes in operating profit and net profit trends as a result of changes in the structure of operating revenues. Conclusion - Total revenues are growing at a slower pace as a result of the changes in business policy and changes in revenue structures than as a result of the impact of the COVID-19 pandemic.